Practical guide to catchment-based water management for the mining and metals industry. (International Council on Mining and Metals, 2015)
This guide has been commissioned to support ICMM members and other interested industry stakeholders to understand the relevance, risks and opportunities of a catchment-based approach to water risk management support companies to define and deliver their own catchment-based water risk management strategies. The guide aims to outline a comprehensive and systematic approach for identifying, evaluating and responding to catchment-based water-related risks. It serves as a structured prompt to guide companies in the development of their water strategies and plans in accordance with the local context and hydrology in which mining and metals operations take place. The guide also aims to complement existing external initiatives and codes, many of which are referenced throughout the document.